2017
DOI: 10.1038/s41598-017-15542-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential T Cell Signaling Pathway Activation by Tacrolimus and Belatacept after Kidney Transplantation: Post Hoc Analysis of a Randomised-Controlled Trial

Abstract: Pharmacokinetic immunosuppressive drug monitoring poorly correlates with clinical outcomes after solid organ transplantation. A promising method for pharmacodynamic monitoring of tacrolimus (TAC) in T cell subsets of transplant recipients might be the measurement of (phosphorylated) p38MAPK, ERK1/2 and Akt (activated downstream of the T cell receptor) by phospho-specific flow cytometry. Here, blood samples from n = 40 kidney transplant recipients (treated with either TAC-based or belatacept (BELA)-based immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Memory T cell signalling is still occurring under immunosuppression because these cells are less reliant on co-stimulatory signals 3336 . For this reason, we can hypothesize about the long lasting persistence of T RM cells within the renal allograft.…”
Section: Discussionmentioning
confidence: 99%
“…Memory T cell signalling is still occurring under immunosuppression because these cells are less reliant on co-stimulatory signals 3336 . For this reason, we can hypothesize about the long lasting persistence of T RM cells within the renal allograft.…”
Section: Discussionmentioning
confidence: 99%
“…Tacrolimus effectively inhibits key T cell activation pathways in T cells after kidney transplant [97]. A rat model of IgAN treated with tacrolimus revealed that usage of CNIs leads to an improvement of clinical features, along with reduction of serum concentration of TGF-β1, Th2-type cytokines (IL-4, IL-5), but elevation of Th1-type cytokine IFN-γ, which might have a protective role against the development of IgAN [98].…”
Section: T Cells As a Therapeutic Target Of Traditional And Biologicamentioning
confidence: 99%
“…Another reason that may contribute to the increased incidence of AR is that belatacept therapy does not inhibit the T-cell activation pathway downstream of the TCR, in contrast to tacrolimus therapy [106]. In a study of 20 belatacepttreated KTRs, no inhibition of the phosphorylation of three important signaling molecules (p38MAPK, extracellular signal-regulated kinases [ERK] 1 and 2, and AKT8 virus oncogene cellular homolog [Akt]) was noted after treatment with belatacept [106]. Furthermore, the phosphorylation of ERK was increased in belatacept-treated patients on days 4 and 90 in patients with an AR compared with patients without an AR [106].…”
Section: Biomarkers Predicting Belatacept-resistant Rejectionmentioning
confidence: 99%
“…In a study of 20 belatacepttreated KTRs, no inhibition of the phosphorylation of three important signaling molecules (p38MAPK, extracellular signal-regulated kinases [ERK] 1 and 2, and AKT8 virus oncogene cellular homolog [Akt]) was noted after treatment with belatacept [106]. Furthermore, the phosphorylation of ERK was increased in belatacept-treated patients on days 4 and 90 in patients with an AR compared with patients without an AR [106]. Prediction of AR was not possible with a targeted proteomic analysis of pre-rejection serum samples of KTRs treated with belatacept [107].…”
Section: Biomarkers Predicting Belatacept-resistant Rejectionmentioning
confidence: 99%